The Geographical Determinants of Within-City Heterogeneity in Urban Density - Melanie Krause; André Seidel (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper studies the impact of building land limitations on within-city variation in urban density and its components crowding, residential coverage, and building height. We utilise geographical obstacles like steep inclines or water bodies as exogenous source of building land limitations within parts of cities. We combine novel high resolution (10m x 10m) geo-spatial data on geography, building height and footprints with Norwegian register data. Our unit of observation are neighborhoods with an average size of 0.3 sqkm. The data indicates a high heterogeneity among the components of urban density for similar total density levels. Our main finding is that local building land limitations increase local urban density and all of its components, with the effect being particularly strong for building heights. Hence, we find support for policies that use building land restrictions to alter urban density within parts of cities. Moreover, we show that geography is another important source of inner-city heterogeneity in urban density, in addition to distance to the city center.
Keywords: R23; R31; R21; C80; 330; urban density; building heights; geography; neighborhoods; inner-city differences